APPLICATION OF BUERGER ALLEN EXERCISE IN PATIENTS WITH INEFFECTIVE PERIPHERAL PERFUSION WITH TYPE II DIABETES MELLITUS AT PASAR REBO JAKARTA HOSPITAL: APPLICATION OF BUERGER ALLEN EXERCISE IN PATIENTS WITH INEFFECTIVE PERIPHERAL PERFUSION WITH TYPE II DIABETES MELLITUS AT PASAR REBO JAKARTA HOSPITAL - Anjani, Syifa; Susanti, Devi; Wiratikusuma, Yohana (STIKes Mitra Keluarga, 2024)
Introduction : Diabetes is a metabolic disease characterized by hyperglycemia due to inability of the pancreas to secrete insulin. Theprevalence of diabetes in the world reaches 422 million people. In Indonesia alone the highest prevalence in DKI Jakarta. Diabetes Mellitus patients are at risk of developing complications, such as nerve damage (neuropathy) and blood vessel disorders (angiopathy). Buerger Allen Exercise is a non-pharmacological therapy aimed at improving blood circulationin in the lower extremities of patients with diabetes mellitus. Method: descriptive qualitative with case study approach and intervention. Result: The results showed that based on the implementation of Buerger Allen Exercise which is carried out for 3 x 24 hours for the second patient, the result on the nursing diagnosis of ineffective peripheral perfusion and the risk of electrolyte imbalance were solved with an initial ABI value of 0,82 increasing to 0,95. However, the problem of unstable blood glucose levels was only partially resolved because the second patient’s blood glucose levels were still very unstable. Conclusion: Both patients experienced an increase in Ankle Brachial Index (ABI) values after performing Buerger Allen exercises,indicating the success of this exercise in addressing nursing problems related to ineffective peripheral perfusion.